PERAN ORANG TUA DALAM MENGHADAPI ARUS PERGESERAN NILAI-NILAI HUMANIS PADA KEHIDUPAN MASYARAKAT MODERN - Muhibbin, Muhibbin (LPPM Institut Pendidikan Nusantara Global, 2021)
This study aims to determine how the role of parents in dealing with the shift in human values ​​in modern society. The type of research in this study was used a qualitative research type with a phenomenological approach. Data collection techniques using observation, interviews, and documentation. The data analysis was used includes three stages, namely data reduction, data presentation and verification/conclusion. The results of the research on factors that influence the inculcation of humanist values ​​in modern society are activities outside the home, parents are too excessive in giving advice, parents also have different jobs and are too restrictive of children with rules. Efforts are made by parents in providing an understanding of human values ​​to their children, such as through example, advice, attention, affection, and discussion. The importance of the parents role was to know in instilling humanist values ​​in children is that children are not easily influenced, know how to act and behave, children are always cared for and believe by their parents.